Blockage of Glyoxalase I Inhibits Colorectal Tumorigenesis and Tumor Growth via Upregulation of STAT1, p53, and Bax and Downregulation of c-Myc and Bcl-2 - Yuan Chen (International Journal of Molecular Sciences, 2017)
GlyoxalaseI (GLOI) is an enzyme that catalyzes methylglyoxal metabolism. Overexpression of GLOI has been documented in numerous tumor tissues, including colorectal cancer (CRC). The antitumor effects of GLOI depletion have been demonstrated in some types of cancer, but its role in CRC and the mechanisms underlying this activity remain largely unknown. Our purpose was to investigate the antitumor effects of depleted GLOI on CRC in vitro and in vivo. RNA interference was used to deplete GLOI activity in four CRC cell lines. The cells’ proliferation, apoptosis, migration, and invasion were assessed by using the Cell Counting Kit-8, plate colony formation assay, flow cytometry, and transwell assays. Protein and mRNA levels were analyzed by western blot and quantitative real-time PCR (qRT-PCR), respectively. The antitumor effect of GLOI depletion in vivo was investigated in a SW620 xenograft tumor model in BALB/c nude mice. Our results show that GLOI is over-expressed in the CRC cell lines. GLOI depletion inhibited the proliferation, colony formation, migration, and invasion and induced apoptosis of all CRC cells compared with the controls. The levels of signal transducer and activator of transcription 1 (STAT1), p53, and Bcl-2 assaciated X protein (Bax) were upregulated by GLOI depletion, while cellular homologue of avian myelocytomatosis virus oncogene (c-Myc) and B cell lymphoma/lewkmia-2 (Bcl-2) were downregulated. Moreover, the growth of SW620-induced CRC tumors in BALB/c nude mice was significantly attenuated by GLOI depletion. The expression levels of STAT1, p53, and Bax were increased and those of c-Myc and Bcl-2 were decreased in the GLOI-depleted tumors. Our findings demonstrate that GLOI depletion has an antitumor effect through the STAT1 or p53 signaling pathways in CRC, suggesting that GLOI is a potential therapeutic target.